Helping Students Navigate Faith Challenges in the Biblical Studies Classroom - Sharp, Carolyn J. (Teaching theology and religion, 2012)
What happens when students encounter the academic study of the Bible in the seminary or undergraduate classroom? Does a teacher have a responsibility to help students navigate challenges to Christian faith that might arise? What pedagogical problems and opportunities does this encounter present? How does this issue manifest differently in undergraduate compared to theological school classrooms? And how are the issues different for students with a strong personal faith commitment compared to students who have never considered the Bible to be relevant to their understanding of themselves and the world? At the 2010 national conference of the Society of Biblical Literature two theological educators, who recently published introductory textbooks, provided brief presentations on this issue. The audience then broke into ten separate conversations roughly organized by institutional type before reconvening for a plenary discussion. The transcript of the presentations and discussion provided here surfaces and juxtaposes the many varied and rich positions that are possible in this topic.